Identification of three cytochrome P450 genes in the Chagas' disease vector Triatoma infestans : Expression analysis in deltamethrin susceptible and resistant populations - Grosso, Carla Gisela (2016)
Cytochrome P450 monooxygenases play a predominant role in the metabolism of insecticides. Many insect P450genes have frequently been associated with detoxification processes allowing the insect to become tolerant orresistant to insecticides. The increases of expression of P450 genes at transcriptional level are often consider responsiblefor increasing the metabolism of insecticides and seems to be a common phenomenon in the evolutionof resistance development in insects. As pyrethroid resistance has been detected in Triatoma infestans, it was ofinterest to analyze genes associated with resistance to insecticides such as those encoding for cytochromesP450. With this purpose, the cDNA sequences of three cytochrome P450 genes (CYP4EM7, CYP3085B1, andCYP3092A6) were identified in this species. Primers and specific Taqman probes were designed from these sequencesto determine their expression by quantitative PCR. The mRNA levels of the cytochrome P450 genes identifiedwere determined from total RNA extracted from pools of fat body collected from individuals of differentresistant and susceptible strains of T. infestans, and at different interval times after the topical application ofthe lethal doses 50% (LD50) of deltamethrin on the ventral abdomen of insects belonging to the different populationsanalyzed. It was detected overexpression of the CYP4EM7 gene in the most resistant strain of T. infestans andthe expression of the three cytochrome P450 genes isolated was induced by deltamethrin in the susceptible andresistant populations included in this study. These results suggest that these genes would be involved in the detoxificationof deltamethrin and support the hypothesis that considers to the cytochrome P450 genes of importancein the development of pyrethroid resistance.